Experimental study on the tribological behavior of ceramic disks for application inmixer taps under different lubrication conditions - Ziegler, Marlene; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Beau, Patrick; Patzer, Gregor; Henzler, Stephan; Marian, Max (Industrial Lubrication and Tribology, 2023)
Purpose – The evaluation of the haptics of water taps and wear-related changes during usage usually involves time- and cost-intensive testing. The purpose of this paper is to abstract the tribo-system between technical ceramic disks of water tap mixer cartridges to the model level and study the tribological behavior. Design/methodology/approach – The friction and wear behavior was studied by means of an alumina ball-on-original alumina disk setup at different temperatures as well as under dry conditions and under lubrication by different greases. Thereby, the frictional behavior was measured in situ, and the wear losses were analyzed by means of laser scanning microscopy. Findings – It was shown that friction and wear can behave in a contrasting way, whereby one grease might lead to low friction, that is, an easygoing movability of the water tap, but to increased wear losses. The latter, in turn, is an indicator for the usability and service life, which cannot be explained from friction alone. Thereby, the viscosity of the base oil, the grease consistency and additives were identified as relevant grease formulation parameters to allow for fluid film (re-)formation and removal of wear particles. Originality/value – To the authors’ best knowledge, this is the first approach to systematically analyze the friction and wear behavior of technical ceramic disks of water tap mixer cartridges in dependency on the temperature as well as the used lubricating grease. This approach is relevant for developing screening test strategies as well as for the selection of lubricants for water tap applications.<br
Keywords: Tribology; Grease; Ceramics; Wear; Friction; Water grade lubricants